The Role of Video to Strengthen Autonomous Learning for Middle High School Students - Rahayu, Pipit; Eripuddin; Sonita, Tiara; Gabriella, Zephanya Ruth (Proceeding of International Conference on Language Pedagogy (ICOLP), 2021)
One of the skills that students need was to learn to be responsible no matter what their age. In this article we intend to turn towards young learners who are still in their middle high school grade think about how we can guide them towards autonomous learning. Students in their middle high school period are natural learners who are driven by curiosity, intrinsic motivation and a desire for exploration. Their innate curiosity gives them satisfaction from learning when they are immersed in an interactive learning environment. Currently, many learning effective and interesting methods are developing, thus students can gain more knowledge in a short time. Video-based learning facilitates in processing information faster, retaining knowledge and remembering it accurately. Methods that being used in this research is library study. We are intended to get to know how video can help the teachers to develop autonomous learning for middle high school student and trying to design classroom activities by using video as a main resource to the student. We hope that other researchers will find other useful medias that can be used in developing autonomous learning.